Verification of the hypotheses on the equality of densities of distributions - Babilua, P.; Nadaraya, E.; Sokhadze, G. A. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We construct new criteria for the verification of the hypotheses that p ≥ 2 independent samplings have identical densities of distributions (homogeneity hypothesis) or identically defined densities of distributions (compatibility hypothesis). We determine the ultimate powers of the constructed criteria for some local “close” alternatives.